2022
DOI: 10.3390/app12126174
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Approach to Predict the Probability of Brain Metastasis in Renal Cell Carcinoma Patients

Abstract: Patients with brain metastasis (BM) have a better prognosis when it is detected early. However, current guidelines recommend brain imaging only when there are central nervous system symptoms or abnormal experimental values. Therefore, metastases are discovered later in asymptomatic patients. As a result, there is a need for an algorithm that predicts the possibility of BM using clinical data and machine learning (ML). Data from 3153 patients with renal cell carcinoma (RCC) were collected from the 11-institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Moreover, several studies have reported on sepsis and malignancy. In the eld of urology, three representative studies were conducted in Korea [11][12][13]. In these studies, several ML algorithms were used, including support vector machines (SVM), logistic regression, random forests, k-nearest neighbors (kNN), XGBoost, AdaBoost, and LightGBM.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies have reported on sepsis and malignancy. In the eld of urology, three representative studies were conducted in Korea [11][12][13]. In these studies, several ML algorithms were used, including support vector machines (SVM), logistic regression, random forests, k-nearest neighbors (kNN), XGBoost, AdaBoost, and LightGBM.…”
Section: Introductionmentioning
confidence: 99%
“…Model-agnostic approaches overcome this limitation and are applicable to any ML model. XAI had been researched for diagnosis and prediction of glioblastoma [ 28 ], colorectal cancer [ 29 ], thoracic cancer [ 30 ], renal cell carcinoma [ 31 ], COVID-19 [ 32 ], chronic wounds [ 33 ], and Alzheimer’s disease [ 34 ]. The use of XAI in medicine is expected to provide insights and transparency into the AI models.…”
Section: Introductionmentioning
confidence: 99%